IMPLEMENTASI PERATURAN BUPATI NOMOR 12 TAHUN 2014 TENTANG PEDOMAN PENGELOLAAN ALOKASI DANA KAMPUNG DI KABUPATEN KUTAI BARAT - Emma Paelongan (Jurnal Administrative Reform, 2019)
The purpose of this study is to describe and analyze the implementation of the Financial Assistance To Village (ADK) Program as well as being inhibiting. The analysis used is the concept of data analysis interactive proposed by Miles, Huberman and Saldana states in qualitative research, data analysis performed by condensation, data presentation and conclusion/verification. The study concluded that the implementation of the ADK Policy relating to communications between actors in the implementation of ADK done through socialization conducted by a team of district to district level and consistency in the achievement of the message/command policy. But some things related to the communication/dissemination to the public about its policies ADK has not been done by the implementor.Keyword: financial, village, implementation